Book Review of The Land and the Song - Rao, Yingqi (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
The Land and the Songs is the first collection of essays by Mr Qiao Jianzhong, a renowned musicology scholar, and a presentation of some of Mr Qiao’s scholarly achievements. This book focuses on traditional Chinese music, covering all aspects of folk songs, raps, and operas.